Investigating Fibromyalgia in Sarcoidosis Patients - Atahan, Ersan; Çalışkaner Öztürk, Buket; Yıldız, Pelin; Asaoğlu, İbrahim; Müsellim, Benan (Cerrahpaşa Medical Journal, 2023)
Objective: Sarcoidosis is a systemic inflammatory disease. Fibromyalgia is a chronic disease that is characterized by widespread musculoskeletal pain, muscle tenderness, fatigue, sleep disturbances, and depression. Fatigue is an integral part of the clinical picture of sarcoidosis. Fatigue and pain are the frequent symptoms in fibromyalgia patients as well as patients with sarcoidosis. This study seeks to determine the prevalence of fibromyalgia, pain, depression, and quality of life in patients with sarcoidosis. Methods: Between January 2015 and June 2015, 39 sarcoidosis patients were included. Patients were evaluated using the Fatigue Severity Scale, fibromyalgia impact questionnaire, Beck’s Depression Inventory, and visual analog scale. The groups with and without fibromyalgia were compared with each other. Results: Fibromyalgia prevalence in sarcoidosis patients is determined to be 43.6% (17/39). Evaluation parameters such as Fatigue Severity Scale, fibromyalgia impact questionnaire, and Beck’s Depression Inventory are statistically significant in fibromyalgia group. Conclusion: The main reason of pain, fatigue, and depression in sarcoidosis patients might be fibromyalgia. If fibromyalgia is considered and diagnosed in the presence of these symptoms, this can help us manage our patients more successfully. Cite this article as: Atahan E, Çalışkaner Öztürk B, Yıldız P, Asaoglu İ, Müsellim B. Investigating fibromyalgia in sarcoidosis patients. Cerrahpaşa Med J. 2023;47(1):14-18.